Langerhans cell antigen capture through tight junctions confers preemptive immunity in experimental staphylococcal scalded skin syndrome - Ouchi, Takeshi (The Rockefeller University Press, 2011)
Epidermal Langerhans cells (LCs) extend dendrites through tight junctions (TJs) to survey the skin surface, but their immunological contribution in vivo remains elusive. We show that LCs were essential for inducing IgG(1) responses to patch-immunized ovalbumin in mice that lacked skin dendritic cell subsets. The significance of LC-induced humoral responses was demonstrated in a mouse model of staphylococcal scalded skin syndrome (SSSS), a severe blistering disease in which the desmosomal protein Dsg1 (desmoglein1) is cleaved by Staphylococcus aureus–derived exfoliative toxin (ET). Importantly, ET did not penetrate TJs, and patch immunization did not alter epidermal integrity. Nevertheless, neutralizing anti-ET IgG(1) was induced after patch immunization and abolished upon LC depletion, indicating that antigen capture through TJs by LCs induced humoral immunity. Strikingly, the ET-patched mice were protected from developing SSSS after intraperitoneal ET challenge, whereas LC-depleted mice were susceptible to SSSS, demonstrating a vital role for LC-induced IgG(1) in systemic defense against circulating toxin in vivo. Therefore, LCs elicit humoral immunity to antigens that have not yet violated the epidermal barrier, providing preemptive immunity against potentially pathogenic skin microbes. Targeting this immunological process confers protection with minimal invasiveness and should have a marked impact on future strategies for development of percutaneous vaccines.